Pengaruh Model Meaningful Instructional Design terhadap Beban Kognitif Konstruktif Siswa SMA: (The Effect of Meaningful Instructional Design on Germane Cognitive Load of High School Students) - Lingga Nurma Mukarromah Lingga; Setiono Setiono; Sistiana Windyariani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the effect of the application of the Meaningful Instructional Design (MID) model on the level of germane cognitive load on high school students in XI degree. The research used pra-experimental method with One Group Pretest-Posttest design as a research design. The data was colected with a written test. The kind of instrument used is the Reasoning Test instrument to measure the score of Learning Outcomes (HB). The data analysis technique used statistical test and independent sample t-test. The sample in this study consisting of one class that was taken using a purpossive sampling technique, in XI MIPA 4 at SMAN 1 Nagrak. The GCL level of students after learned using the Meaningful Instructional Design model was in the tended to be high category with the average score of HB=73.68 and the acquisition of sig. (2-tailed) is 0.00<0.05 for the independent sample t-test result. Based on the students' average Learning Outcomes scores and sig. (2-tailed) on the hypothesis test, it can be concluded that there is a significant positive effect with the application of the Meaningful Instructional Design model on the germane cognitive load of high school students. Keywords : Germane Cognitive Load, Meaningful Instructional Design. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh dari penerapan model Meaningful Instructional Design (MID) terhadap tingkat beban kognitif konstruktif siswa SMA kelas XI. Jenis penelitian yang digunakan adalah pra-experimental dengan desain penelitian One Group Pretest-Posttest. Teknik pengumpulan data menggunakan tes tertulis. Isntrumen yang digunakan yaitu instrumen Tes Penalaran untuk mengukur skor Hasil Belajar (HB). Teknik analisis data menggunakan uji statistik dan uji dua rerata (Independent Sample T-Test). Dengan sampel dalam penelitian ini yang terdiri dari satu kelas yang diambil menggunakan teknik purpossive sampling, yaitu pada kelas XI MIPA 4 di SMAN 1 Nagrak. Tingkat GCL siswa setelah mendapatkan prmbelajaran menggunakan model Meaningful Instructional Design (MID) berada dalam kategori cenderung tinggi dengan skor rata-rata HB=73.68 dan perolehan nilai sig. (2-tailed) 0,00<0,05 untuk hasil uji independent sample t-test. Berdasarkan nilai rata-rata Hasil Belajar siswa dan sig. (2-tailed) pada uji hipotesis dapat disimpulkan bahwa terdapat pengaruh positif yang signifikan dari penerapan model Meaningful Instructional Design terhadap beban kognitif konstruktif siswa SMA. Kata Kunci : Beban Kognitif Konstruktif, Meaningful Instructional Design